Brand against the machine : how to build your brand, cut through the marketing noise, and stand out from the competition - Morgan, John , 1961- (John Wiley & Sons, 2012)
"Ditch traditional corporate branding to create a powerful, recognizable brand. Brand Against the Machine offers proven and actionable steps for companies and entrepreneurs to increase their brand visibility and credibility, and to create an indispensable brand that consumers can relate to, thus becoming life-long customers. Discover the aspirational currency that makes your brand one that people want to be or want to be friends with. Learn how to be real with your audience and make strategic associations to establish credibility. Brand Against the Machine will help you stand out, get noticed, and be remembered. Brand Against the Machine is the blueprint for how to market your brand to attract better clients and stand out from the clutter that is traditional corporate branding and marketing. Instant Positioning Method: How to instantly stand out from the crowd and position yourself as a resource, not just another service provider The 20/60/20 Rule: Why it's important to take a stand and why it's okay to have haters--because it creates a stronger bond with those who love you. Ditch your traditional corporate branding and marketing, and exchange it for something memorable. Your customers will thank you for it"--Provided by publisher.